Learning Difficulties and Students' Ability Level During Pandemic Covid-19 on the Subject of Thermochemistry - Agustina, Rizza R. T.; Afadil, Afadil; Rahmawati, Sitti; Tiwow, Vanny M. A. (Universitas Tadulako, 2023)
This study aims to identify learning difficulties learning experienced by students on the subject thermochemistry in class XI IPA SMA Negeri 8 Palu during the Covid-19 pandemic for the 2021 / 2022 school year. The instruments used in this study are thermochemistry tests, questionnaires, and interviews. The result showed students’ difficulties in the subject thermochemistry in class XI IPA was 60 %, the highest difficulty of students is found in the thermochemistry test of calculating the heat of the type of compound, calculating enthalpy changes, and formulating steps and hypotheses of an experiment. The difficulty is indicated by the low level of student comprehension of 54 %, medium 43 %, and high 3 % with an average of 30%. Furthermore, the difficulty of students in participating in chemistry learning during the Covid-19 pandemic is technical difficulties with a percentage of 65.92 %, difficulties in implementing learning with a percentage 0f 65.44 %, and external difficulties (environment and parents) with a percentage of 52.92 %. based on these results, the learning difficulties experienced by students during chemistry learning thermochemistry subjects during the Covid-19 pandemic include students often being constrained by signals and quotas to access materials on the internet and do not have student handbooks to study at home, difficulty understanding chemistry concepts because teacher explanations are elusive, students are not active in participating in learning because chemistry learning during the pandemic is not interesting, can’t afford chemistry books and quotas also parents don’t provide motivation and students are often lazy to do assignments because no one helps with doing. The result of this study indicates that the level of students' difficulties learning about thermochemistry is a quite high category with a low level of student ability and students agree that it is difficult to study chemistry during the pandemic Covid-19.